The nexus between European funds, economic growth and government quality in the EU - Cigu, Elena (Central European Public Administration Review, 2025)
The purpose of this paper is to identify the contextual associations between the absorption of European funds, economic growth, and the quality of governance. The structural funds of the European Union support the strengthening of the economies of its Member States. The efficient use of these funds is achieved through high-quality governance; however, efficient governance presupposes a stable and developed economy. Design/Methodology/Approach: The methodological background comprises a qualitative sequential approach involving a literature review and empirical analysis that provide coherence and viability for the study. We mainly employ quantitative methods, including an econometric model based on panel data for European countries over the period 2007–2020, which represents a novel approach in the literature. Findings: The empirical results indicate a positive relationship between the European funds absorption rate, economic growth, and institutional governance factors. Originality/Value: The article may be considered a useful contribution to understanding the complex relationship between European funds, government quality, and economic growth, thus adding to the existing literature.
Keywords: črpanje evropskih sredstev; economic growth; European funds absorption; gospodarska rast; government quality; kakovost upravljanja